Directed, Palladium(II)-Catalyzed Enantioselective anti-Carboboration of Alkenyl Carbonyl Compounds - Liu, Zhen; Li, Xiaohan; Zeng, Tian; Engle, Keary M (ACS catalysis, 2019)
A substrate-directed enantioselective anti-carboboration reaction of alkenes has been developed, wherein a carbon-based nucleophile and a boron moiety are installed across the C=C bond through a 5-membered palladacycle intermediate. A preliminary result also shows it is possible to extend this reaction to alkenes that are more distal from the directing group and react via a 6-membered palladacycle. The reaction is promoted by a palladium(II) catalyst and a monodentate oxazoline ligand. A range of enantioenriched secondary alkylboronate products were obtained with moderate to high enantioselectivity that could be further upgraded by recrystallization. This work represents an efficient method to synthesize versatile and valuable alkylboronate building blocks. Building on an earlier mechanistic proposal by Peng, He, and Chen, a revised model is proposed to account for the stereoconvergent nature of this transformation.